Gdy cesarzowa piła herbatę... Historia chińskiego jedwabiu od neolitu do czasów panowania dynastii Tang - Kossowska-Janik, Dominika (Studia Azjatystyczne, 2017)
Chinese silk has a long history. The sericulture began in Neolithic times. Before the Western Zhou period (1600-1046 BC) the most popular textiles were plain weaved (juan) and gauzes (sha and luo). During the kingship of the Zhou dynasty (Western and Eastern) new types of textiles began to be woven, for example: pseudo-damasks (qi and han qi) and warp faced compound tabby (jin). The most beautiful four-color, and five-color jin fabrics were woven in Han dynasty (206 BC-220 AD). In this period China came in contact with the Western world. It was the beginning of the so-called Silk Road. Weaving technique still flourished during the next periods. The first samit textiles (often decorated with Persian motives) were weaved during the Tang dynasty. The sericulture was a ritual practiced in the common households and royal courts. The silkworm had its own temples and goddess.